Economic assessment of an intervention strategy to reduce antimicrobial usage in small-scale chicken farms in Vietnam - Truong Dinh Bao; Nguyen Van Cuong; Nguyen Nhu Mai; Le Thi Thu Ha; Doan Hoang Phu; Bach Tuan Kiet; Juan Carrique-Mas; Jonathan Rushton (One Health, 2024)
Antimicrobials are a core aspect of most livestock production systems, especially in low-and middle-income countries. They underpin the efficient use of scarce feed resources and stabilize returns on capital and labor inputs. Antimicrobial use (AMU) contributes to the production of healthy animals, yet AMU in livestock is linked to antimicrobial resistance (AMR) in animals, humans and the environment.The Vietnamese Platform for Antimicrobial Reduction in Chicken Production was implemented during 2016–2019 and was one of Southeast Asia's first interventions focused on AMU reductions in livestock production. The project targeted small-scale commercial poultry farms in the Mekong Delta region of Vietnam using a “randomized before-and-after controlled” study design. It provided farmers with a locally adapted support service (farmer training plan, advisory visits, biosecurity, and antimicrobial replacement products) to help them reduce their reliance on antimicrobials. A partial budget analysis was performed comparing the control group (status-quo) and intervention group (alternative). The median net farm-level benefit of the intervention strategies with the project's support was VND 6.78 million (interquartile range (IR) VND -71.9–89 million) per farm. Without project support the benefit was reduced to VND 5.1 million (IR VND -69.1–87.2 million) to VND 5.3 million (IR -VND 68.9–87.5 million) depending on the antimicrobial alternative product used. At the project level with a focus on AMU and its reduction, subsequently influence on the resistance reduction, our results showed that achieving resistance reduction benefits with the current knowledge and technologies required investment of at least VND 9.1 million (US$ 395.10) per farm during the project's lifetime. The results highlight the positive net profit for the majority of enrolled farms and a reasonable investments from the project. The recommendation focuses on the implementation of policies on financial support, legislation, and information as potential solutions to facilitate the application of intervention strategies to reduce AMU in poultry production.